Homeschooling Tunggal sebagai Pembelajaran Alternatif: Studi Kasus Homeschooling Suka-Suka - Hawa, Aprilia Puji; Ahnaf , Muhammad Dhiauddin (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2022)
Homeschooling Single homeschooling is a model of home-based education that is carried out by a family. Parents have the role of being responsible and the main manager in their child's education. The purpose of this study is to find out how the implementation of homeschooling and how this can be an initial capital for developing youth potential for sustainable innovation. Descriptive qualitative methods are used to describe the meaningfulness of learning in homeschooling. In a case study conducted at Homeschooling Suka-Suka, a curriculum based on child psychology guidelines, growth and development guidelines, school curriculum and religious curriculum. In compiling the curriculum, parents divide it based on the age level of children's education in general. Learning is carried out based on skill practice and adapted to the interests of students. There are main lessons and additional lessons in each semester so that students are more focused on what they are learning. In addition, students are also still included in state exams, so that learning outcomes are still recognized and get diplomas. Furthermore, learning outcomes that are not listed in the state exam will still receive an accredited certificate of knowledge, experience and skills. Learning in homeschooling emphasizes the formation of skills in the fields of communication, networking, creativity and innovation. This learning system helps students in developing and improving their learning outcomes because learning is done by adjusting the needs of the students themselves. So that learning becomes more meaningful, on target and sustainable. This can be an initial capital to strengthen the development of youth potential and build sustainable innovation in the future.